Solve for x: 3^(4x-3)*5^(7x-4)=3^3x*5^(8x-7).
- print Print
- list Cite
Expert Answers
calendarEducator since 2010
write12,544 answers
starTop subjects are Math, Science, and Business
We have to solve for x given the equation: 3^(4x-3)*5^(7x-4)=3^3x*5^(8x-7)
3^(4x-3)*5^(7x-4)=3^3x*5^(8x-7)
=> 3^4x*3^-3*5^7x*5^-4 = 3^3x*5^8x*5^-7
=> (3^4x/3^3x)*(3^-3)*(5^7x/5^8x)*(5^-4/5^-7) = 1
=> (3^x)*(3^-3)*(1/5^x)*(5^3) = 1
=> (3/5)^x = (3/5)^3
As the base is equal we equate the exponent.
=> x= 3
The required value of x is x = 3.
Related Questions
- Solve for x: 4(3x+7)=7
- 2 Educator Answers
- Solve for x and y 3x+y = 5 x-2y=4Solve for x and y 3x+y = 5 x-2y=4
- 1 Educator Answer
- log 2 (2x) + log 4 (4x^2) = 3 solve for x
- 1 Educator Answer
- Solve 2x+3y=7 3x+2y=4 for x and y.
- 1 Educator Answer
- Solve: log 2 (3x ) - log 4 ( x-2) = 3
- 1 Educator Answer
We'll divide both sides by 5^(7x-4) and 3^3x:
3^(4x-3)/3^3x = 5^(8x-7)/5^(7x-4)
We'll subtract the exponents: 3^(4x - 3 - 3x) = 5^(8x - 7 - 7x + 4)
We'll combine like terms inside brackets: 3^(x - 3) = 5^(x - 3)
We'll re-write the equation:
3^x*3^-3 = 5^x*5^-3 3^x/3^3 = 5^x/5^3
We'll create matching bases.
We'll divide by 5^x:
3^x/5^x*3^3 = 1/5^3
We'll multiply by 3^3:
3^x/5^x = 3^3/5^3 (3/5)^x = (3/5)^3
Since the bases are matching, we'll apply one to one property:
x = 3
The solution of the equation is x = 3.
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.
Student Answers